Learning Resources by Environment sebagai Visualisasi Manajemen Sarana Prasarana Pendidikan di MIN Jejeran Bantul - Siti Nadhiroh; Rina Roudhotul Jannah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This research is based on the recent development and progress of the educational world which urgently requires the improvement of the educators' creative power. The representation of educators' competence and their credibility can be ascertained not only from their ability in completing teaching-related-task in short time range but also their effective strategy in optimising facilities hence creating school's learning resources by environment.. The research is a qualitative study employing MIN Jejeran Bantul Yogyakarta as the subject of the study. The results show that facilities and infrastructures management, including planning, stock taking, usage, maintenance, removal, and responsibility distribution improve educator's creativity as well as enrich scientific treasure which further can be integrated into learning. Eventually, it leads to students' developed morality in preserving surrounding environment